DEKONSTRUKSI ISTINBAth ala Kaum Liberal - Wafi Muhaimin (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2017)
Penelitian ini bertujuan untuk menguji secara kritis kaidah ushul fiqih kaum liberal dan aplikasinya dalam buku Counter Legal Draft Kompilasi Hukum Islam  (CLD-KHI), yang dicanangkan untuk menjadi buku pedoman peradilan Agama di Indonesia. Kaidah kaum liberal mendiskusikan kaidah ushul fiqih yang sangat mendasar, yaitu maqa>s}id, mashlahah dan akal, serta implementasinya dalam hukum keluarga (al-ahwa>l al-shakhs}iyah). Agar persoalan ini menjadi jelas, dalam mengkaji kaidah ushul fiqih dan fiqih kaum liberal, peneliti menggunakan metode induktif dan analisis-kritis, dengan pendekatan karya ulama ushul fiqih dan fuqaha. Dari kajian ini, dapat disimpulkan bahwa kaidah ushul fiqih kaum liberal bukanlah kaidah baru, melainkan mengadopsi kaidah kontroversi (terdahulu) untuk meruntuh- kan teks-teks agama (nus}u>s}) atas nama maqa>s}id, mas}lahah dan akal, yang tercermin dari fiqih yang dihasilkan dari kaidah ini dan tertuang dalam CLD-KHI dengan cara menyandarkan terhadap pendapat yang lemah The study aims to critically examine the rules of the principles of jurisprudence propagated by the liberalists and their application in Counter Legal Draft-Kompilasi Hukum Islam (CLD-KHI), which has been developed as an endeavour to supersede the guiding texts used in religious courts in Indonesia. Their principles of jurisprudence are devoted to discussing the fundamental concept of ushul al-fiqh, covering the subject of maqa>s}id (objectives), mas}lahah (public benefit) and 'aql (logic), using difficult steps in problematic approaches. Furthermore, the application of the principles of jurisprudence dealing with issues related to the civil matters adopted atypical views. Against this backdrop, the present study undertakes to review the liberalists’ legal maxims using both inductive and critical-analytical methodologies from ushul al-fiqh and fiqh approaches. The findings of the study reveal that the maxims propagated by the liberalists are not something new. In fact, they are derived and adapted from anomalous maxims to disregard and revise the divine revelation by misusing the concept of maqa>s}id, mas}lahah and over reliance upon the logic. Most of the maxims’ applications found in CLD-KHI refer to the weak opinions.